The intensity of supplementary feeding in an urban environment impacts overwintering Mallards (Anas platyrhynchos) as wintering conditions get harsher - Marta Witkowska; Wojciech Wesołowski; Martyna Markiewicz; Jonasz Pakizer; Julia Neumann; Agnieszka Ożarowska; Włodzimierz Meissner (Avian Research)
Although urbanization poses various threats to avifauna, some bird species, including Mallards (Anas platyrhynchos), choose towns and cities as their wintering habitats, possibly due to favourable temperatures and abundant anthropogenic food. In this study, we investigated how population dynamics changed in relation to winter harshness and intensity of supplementary bird feeding in Mallard, a dabbing duck species well adapted to an urban environment. We surveyed 15 city ponds for five consecutive years, counting overwintering individuals and incidents of bird feeding conducted by the citizens of Gdańsk. Number of Mallards observed in the studied area fluctuated both annually and within seasons, with on average 327 (± SD = 108.5) individuals and a male-biased sex ratio reported. We observed a gradient of feeding intensity on the surveyed ponds, with number of feeding incidents ranging from 0 to 30 in a day. The results indicated that the number of Mallards increased with the bird feeding intensity, independently of the size of the studied ponds, and both males and females were similarly attracted by food provisioning. More severe wintering conditions, expressed by the percentage of the ice cover of studied ponds resulted in more birds wintering in the urban area. This effect was more pronounced in females compared to males, possibly due to females having a lower ability to withstand severe wintering conditions, forcing them to relocate towards urban areas. Our results confirm that urbanized areas may serve as wintering grounds for birds, due to additional food resources available there and milder wintering conditions compared to surrounding rural areas.